Surface chemistry effects on heterogeneous clathrate hydrate nucleation: A molecular dynamics study. (February 2018) - DeFever, Ryan S.; Sarupria, Sapna
Graphical abstract: Highlights: We study the effects of surface hydrophobicity on clathrate hydrate nucleation. –CH3 and –OH terminated self-assembled monolayers are used as model surfaces. We generated 30 nucleation trajectories with molecular dynamics simulations. Hydrate nucleation always occurred homogenously, >1 nm from either surface. Primary surface effects on hydrate nucleation came from their effect on local guest concentration. Abstract: We report results from a molecular dynamics study of clathrate hydrate nucleation near model hydrophilic and hydrophobic surfaces. –CH3 and –OH terminated self-assembled monolayers (SAMs) are used as model surfaces. We study the nucleation of a soluble, structure II forming guest molecule with a coarse-grained model compatible with monatomic water. Despite the presence of SAMs, we show that nucleation occurs through a homogeneous mechanism in OHSAM and CH3 SAM systems. Formation of ice-like or intermediate water structure is not observed near either surface prior to nucleation. Nucleation occurs more quickly in OHSAM systems than CH3 SAM systems. However, the faster nucleation is driven by a partitioning of guest molecules which results in higher bulk guest concentration in OHSAM systems compared with CH3 SAM systems. Despite significant aggregation of guest molecules near CH3 SAM, no nucleation is observed near the surface. The formation of guest contact pairs, facilitated by the presence of CH3 SAM, may prevent nucleation in this region. Our results highlight the numerous routes by which surfaces can affect hydrate nucleation due to the multicomponent nature of the phenomena.